British Intelligence and Transnational Anti-colonialists: Subhas Chandra Bose and Sir Roger Casement Compared - O'Halpin, Eunan (My University, 2024)
This article discloses and compares how British intelligence organisations were able, through intercepting and decoding the secret communications of rival powers - Germany in the First World War, Germany, Italy and Japan during the Second World War - to discover and monitor key aspects of anti-colonial intrigue between, respectively, the Irish rebel Sir Roger Casement in 1916, and the Indian separatist leader Subhas Chandra Bose from 1940 to 1945. It also demonstrates how the British government used such material in 1941 to plan the assassination of Bose as he passed through neutral Turkey en route to the Soviet Union. In fact, between February and June 1941 Bose travelled via the Central Asian Soviet republics to Moscow and then on to Berlin. The article also shows that in 1943 the British were aware of detailed arrangements made to transfer Bose from a German to a Japanese submarine off Madagascar, but decided not to attempt an interception for fear that this action would alert the Axis powers to the vulnerability of their cipher systems.
PUBLISHED
Keywords: Codebreaking; Irish Separatism; Indian Separatism; Roger Casement; Subhas Chandra Bose; Codebreaking; Irish Separatism; Indian Separatism; Roger Casement; Subhas Chandra Bose; Identities in Transformation; International Integration; Making Ireland